A New discrete cosine transform on face recognition through histograms for an optimized compression - Fatma Susilawati, Mohamad; Zahraddeen, Sufyanu; Abdulganiyu Abdu, Yusuf (Academic Journals Inc, 2015)
Images with reduced signal level that can be easily stored in a database for recognition purposes are highly demanded. A system with large capacity requires a highly compressive technique for its efficiency. In this study, more efficient image compression algorithm was disclosed which reduced the size of original image drastically. After the necessary preprocessing, the histogram plot of an image was obtained. This histogram was rotated by 45° to produce a reduced image. Therefore, the two-dimensional Discrete Cosine Transform (2DCT) was computed on the rotated histogram to produce a new matrix. However, the proposed framework was tested on ten subjects from Olivetti Research Laboratory (ORL) database and its performance was evaluated using compression parameters such as PSNR and MSE. The new framework results in better reconstruction error and better PSNR values than original JPEG compression level. The new DCT matrix is proposed to proceed for postprocessing in DCT domain, where several coding approaches are employed. It was believed that, this discovery is new in the field of signal processing.